Iowa Birdline update, August 22, 1994 - Fuller, James L.et al; Iowa Ornithologists' Unionet al (1994)
Email of the Iowa Birdline update for August 22, 1994. Highlights of the update include sightings of numerous Warbler species and shorebirds as well as the continued presence of a Pacific Loon. Other observations of note include a Henslow's Sparrow, Red-necked Phalarope, Sandhill Cranes, and Burrowing Owls. Epson - sheet feed/flatbed